Desenvolvimento de um sistema digital em um equipamento para tratamento de sementes - Levandoski, Joan Michel (2017)
Seed treatment is a practice used to allow it to germinate and grow in a healthy way. The increasing search for treated seeds, sold by traders, has caused a market demand arise for machines for this type of production. In view of this need, this research had as objective to apply methodologies and techniques for the development of an equipment capable of performing the automatic control of inputs applied in the industrial treatment of seeds, developing a friendly interface between man and machine for the application and withdrawal of information from the process. It also proposed the construction of a prototype that, when finished, made possible the execution of tests with the seed and evaluations of the process. With the construction of the prototype, the testing and assay of the equipment began. This was submitted to four types of assays. It was initiated by the input conformity assay, that had as goal to evaluate whether the inputs applied by the peristaltic pumps were consistent with the values set by the operator. After this, the second assay was carried out, in order to prove the leakage of the pump system. This assay showed that the pumping system does not provide syrup return. The third test aimed the compliance in the volume of seeds controlled by the equipment, where it performed the control of grain intake accurately, obtaining little variability. Finally, a test aiming to verify the homogeneity of the application of the inputs. This test used two cultivars with different treatments. Performed the analysis, the results obtained were different for each cultivar. It is also worth noting the approval of the treatment performed by the equipment in four analyzes carried out by the laboratory The Seedcare Institute. Based on the tests carried out, it was possible to state that the equipment is ready to be produced and marketed.